Assessing muscle‐specific potassium concentrations in human lower leg using potassium magnetic resonance imaging. (5th September 2022) - Gast, Lena V.; Baier, Laura‐Marie; Chaudry, Oliver; Meixner, Christian R.; Müller, Max; Engelke, Klaus; Uder, Michael; Heiss, Rafael; Nagel, Armin M.
Abstract : Noninvasively assessing tissue potassium concentrations (TPCs) using potassium magnetic resonance imaging ( 39 K MRI) could give valuable information on physiological processes connected to various pathologies. However, because of inherently low 39 K MR image resolution and strong signal blurring, a reliable measurement of the TPC is challenging. The aim of this work was to investigate the feasibility of a muscle‐specific TPC determination with a focus on the influence of a varying residual quadrupolar interaction in human lower leg muscles. The quantification accuracy of a muscle‐specific TPC determination was first assessed using simulated 39 K MRI data. In vivo 39 K and corresponding sodium ( 23 Na) MRI data of healthy lower leg muscles (n = 14, seven females) were acquired on a 7‐T MR system using a double‐resonant 23 Na/ 39 K birdcage Tx/Rx RF coil. Additional 1 H MR images were acquired on a 3‐T MR system and used for tissue segmentation. Quantification of TPC was performed after a region‐based partial volume correction (PVC) using five external reference phantoms. Simulations not only underlined the importance of PVC for correctly assessing muscle‐specific TPC values, but also revealed the strong impact of a varying residual quadrupolar interaction between different muscle regions on the measured TPC. Using 39 K T2 * decay curves, we found significantly higher residual quadrupolar interaction in tibialis anterior muscle (TA; ωq  = 194 ± 28 Hz) compared with gastrocnemius muscle (medial/lateral head, GM/GL; ωq  = 151 ± 25 Hz) and soleus muscle (SOL; ωq  = 102 ± 32 Hz). If considered in the PVC, TPC in individual muscles was similar (TPC = 98 ± 11/96 ± 14/99 ± 8/100 ± 12 mM in GM/GL/SOL/TA). Comparison with tissue sodium concentrations suggested that residual quadrupolar interactions might also influence the 23 Na MRI signal of lower leg muscles. A TPC determination of individual lower leg muscles is feasible and can therefore be applied in future studies. Considering a varying residual quadrupolar interaction for PVC of 39 K MRI data is essential to reliably assess potassium concentrations in individual muscles. Abstract : The feasibility of tissue potassium concentration (TPC) determination in individual lower leg muscles using 39 K MRI at 7 T was evaluated in 14 healthy subjects. For quantification, we propose a region‐based partial volume correction approach using tissue masks extracted from high‐resolution 1 H MRI data in combination with an individual signal decay for each muscle region. Overall, a strong influence of the residual quadrupolar interaction on the measured TPC was observed.